The ethanol metabolite acetic acid activates mouse nucleus accumbens shell medium spiny neurons - Chapp, Andrew D. (J Neurophysiol, 2021)
Although ethanol consumption leads to an array of neurophysiological alterations involving the neural circuits for reward, the underlying mechanisms remain unclear. Acetic acid is a major metabolite of ethanol with high bioactivity and potentially significant pharmacological importance in regulating brain function. Yet, the impact of acetic acid on reward circuit function has not been well explored. Given the rewarding properties associated with ethanol consumption, we investigated the acute effects of ethanol and/or acetic acid on the neurophysiological function of medium spiny neurons of the nucleus accumbens shell, a key node in the mammalian reward circuit. We find that acetic acid, but not ethanol, provided a rapid and robust boost in neuronal excitability at physiologically relevant concentrations, whereas both compounds enhanced glutamatergic synaptic activity. These effects were consistent across both sexes in C57BL/6J mice. Overall, our data suggest acetic acid is a promising candidate mediator for ethanol effects on mood and motivation that deserves further investigation. NEW & NOTEWORTHY Ethanol consumption disrupts many neurophysiological processes leading to alterations in behavior and physiological function. The possible involvement of acetic acid, produced via ethanol metabolism, has been insufficiently explored. Here, we demonstrate that acetic acid contributes to rapid neurophysiological alterations in the accumbens shell. These findings raise the interesting possibility that ethanol may serve as a prodrug—generating acetic acid as a metabolite—that may influence ethanol consumption-associated behaviors and physiological responses by altering neurophysiological function.